Principle of Horizontal Separation in Registration of the Former Western Rights Land as the Object of Afwezigheid - Yulita Dwi Pratiwi (Badan Strategi Kebijakan Hukum, 2022)
The Job Creation Law affects some policy changes in agrarian sector. For instance, the promulgation of Government Regulation No 18 of 2021 (GR 18/2021) regulates that former western rights land are adjusted to state land. However, some former western rights land have not been converted until now. It results in legal uncertainty over the land status, especially land or building juridically belong to the person declared absent (afwezigheid) yet owned by legal subjects. This study aims to analyze the land rights registration of former western rights land after the Job Creation Law. Besides, it analyzes the implementation of horizontal separation principle in the land rights registration of former western rights land and buildings, that are the object of afwezigheid. This study is legal research applying statute, historical and conceptual approaches. Based on the study, people who possessed former western rights land are the main priority in applying for land rights regarding to GR 18/2021 article95. Meanwhile, those who only occupy the land and building have to get afwezigheid court decision of the former western rights land owner. Afterwards, they follow the object buying process with the principle of horizontal separation through Probate Office and submit land rights application at the land registry office.